Secondary labial cryptococosis in immunocompetent patient: case report - Marcucci, Marcelo; Costa, Anderson Costa Lino; Cappellano, Elaine Cristina (Journal of Oral Diagnosis, 2020)
Cryptococcosis is a fungal infection that produces skin lesions, and more rarely, oral lesions, which are usually secondary to lung and central nervous system involvement. It mainly affects immunosuppressed patients. A 26-year-old patient without comorbidities was diagnosed with central nervous system cryptococcosis, confirmed by detecting fungus in the cerebrospinal fluid, and presenting with an ulcerated single semi-mucosal lip nodule. The anatomopathological study of the lip lesion showed morphology compatible with Cryptococcus spp., confirmed by Grocotts staining. The patient was treated with antifungals and progressed satisfactorily. This is a case report of a rare semi-mucosal lip lesion and its possible origin.